Microbiology of the Human Intestinal Tract and Approaches for Its Dietary Modulation - Saulnier, Delphine M.; Kolida, Sofia; Gibson, Glenn R. (Current Pharmaceutical Design, 2009)
Gut bacteria can be categorised as being either beneficial or potentially pathogenic due to their metabolic activities and fermentation end-products. Health-promoting effects of the microflora may include immunostimulation, improved digestion and absorption, vitamin synthesis, inhibition of the growth of potential pathogens and lowering of gas distension. Detrimental effects are carcinogen production, intestinal putrefaction, toxin production, diarrhoea/constipation and intestinal infections. Certain indigenous bacteria such as bifidobacteria and lactobacilli are considered to be examples of health-promoting constituents of the microflora. They may aid digestion of lactose in lactose-intolerant individuals, reduce diarrhoea, help resist infections and assist in inflammatory conditions. Probiotics, prebiotics and synbiotics are functional foods that fortify the lactate producing microflora of the human or animal gut.